Brighton v Will: The Legal Chasm between Animal Welfare and Animal Suffering - Sophie Riley (Animals, 2020)
Through the mechanism of statutory interpretation, courts can narrow or widen the legal concept of animal cruelty. This was starkly brought to light in the case of Brighton v Will, where the Supreme Court of New South Wales held that stabbing a dog six times with a pitchfork and then killing him with a mallet, did not amount to serious animal cruelty. This finding was the result of the Court’s applying a textual interpretation to the NSW Crimes Act, concluding that the appellant was simply exterminating a pest. Yet, animal law in NSW comprises more than legislation, extending to a raft of plans and strategies which provide background and context for regulation. This article argues that a contextual interpretation would have been more appropriate, leading to enquiries whether the dog was rightfully classified as a pest, as well as whether the law should have considered the manner in which the dog was killed. An equally relevant issue stems from the relationship between animal suffering and animal welfare, a connection which hinges on the ambit of anti-cruelty legislation. The latter permits a range of exceptions and defences that permit justification of cruelty, magnifying the chasm between animal suffering and animal welfare. This chasm is also not diminished by legal interpretations of cruelty that focus on whether killing is justified, while ignoring the method of killing.